2020
DOI: 10.1155/2020/5735279
|View full text |Cite
|
Sign up to set email alerts
|

Decreased ALKBH5, FTO, and YTHDF2 in Peripheral Blood Are as Risk Factors for Rheumatoid Arthritis

Abstract: ALKBH5 (alkylation repair homolog protein 5), FTO (fat mass and obesity-associated protein), and RNA N6-methyladenosine (m6A) demethylase, are essential for the m6A mRNA modification. YTHDF2 (YT521-B homology domains 2) called m6A “readers” can recognize m6A modification. As the key enzymes of m6A methylation modification, ALKBH5, FTO, and YTHDF2 have been implicated in many diseases. However, little is known about the role of ALKBH5, FTO, and YTHDF2 in rheumatoid arthritis (RA). We measured the mRNA expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 30 publications
3
53
0
Order By: Relevance
“… 13 , 14 With the deepening of research and the rapid development of technology, it has been found that there is an association between m6A methylation and RA. Luo et al 15 confirmed that the expression of peripheral blood ALKBH5 and FTO was linked with autoantibody production and RA disease activity, which may be used as an indicator of activity and the inflammatory response. However, there are few studies about the effect of m6A methylation on RA FLSs.…”
Section: Introductionmentioning
confidence: 96%
“… 13 , 14 With the deepening of research and the rapid development of technology, it has been found that there is an association between m6A methylation and RA. Luo et al 15 confirmed that the expression of peripheral blood ALKBH5 and FTO was linked with autoantibody production and RA disease activity, which may be used as an indicator of activity and the inflammatory response. However, there are few studies about the effect of m6A methylation on RA FLSs.…”
Section: Introductionmentioning
confidence: 96%
“…These relatively weighty postulations suggesting detectable involvement of epitranscriptomics with the atherosclerosis-stimulated clonal hematopoiesis rest on several notions: (1) driver mutations for clonal hematopoiesis in HSCs, when present, often reside in epigenetic or epitranscriptomic targets [ 83 ], and (2) multiple governing enzymes of A-to-I [ 84 ] and m 6 A [ 31 , 85 , 86 , 87 , 88 ] have been shown to be essential for maintaining normal hematopoiesis. Finally, as proof-of-principles, emerging evidence suggests blood epitranscriptomes to act as potential source of biomarkers for coronary atherosclerosis and thus IHD [ 151 ], breast [ 165 ], gastric [ 166 ], and lung [ 167 ] cancers as well as for few other inflammation-centered pathologies than IHD, such as systemic lupus erythematosus [ 168 ] and rheumatoid arthritis [ 169 ].…”
Section: Discussionmentioning
confidence: 99%
“…YTHDF2 mRNA expression was shown to be correlated with L%, N%, RBC, NLR, and LMR. Moreover, logistic regression analysis suggested that reduced ALKBH5, FTO, and YTHDF2 expression in PBMCs is a risk factor for RA (Luo et al, 2020 ). Another study revealed that METTL3 expression is significantly increased in the PBMCs of RA patients (Wang J. et al, 2019 ).…”
Section: A Modification In Cells Involved In Rmentioning
confidence: 99%